Serum levels of LDH and protein/creatinine index in pregnant women with preeclampsia: A single-center retrospective study - Moya-Salazar, Jeel (2022)
“Introduction: Preeclampsia is the major cause of maternal death in Latin America, which presents with hypertension and proteinuria after 20 weeks of gestation, increasing the levels of inflammatory markers.We aimed to determine the ratio of LDH and protein/creatinine index (PCI) in Peruvian pregnant women with preeclampsia at the Hospital Nacional Docente Madre Niño San Bartolomé in 2017. Materials and methods: we conducted a cross-sectional study in 3415 pregnant preeclamptic women without eclampsia or HELLP syndrome. The kinetic method was used to determine urine creatinine (mg/dl), the turbidimetric method for protein quantification (mg/dl), and the kinetic method for LDH (U/L). Kendall’s Tau-b correlation and non-paired t-test were used. Results: Of the total, 168 (4.9%) had a clinical diagnosis of preeclampsia with a higher frequency in the 25-35 age group (41.7%). We observed 9-fold frequency of multiparous pregnant women (p<0.001). In 121 (72%) pregnant women, LDH was elevated (>414 U/L). The mean LDH was 536±206.7 U/L (range: 264 to 1715 U/L). Seventy-two (42.9%) pregnant women had LDH values between 416-599 U/L, 37 (22%) had LDH values between 600-800 U/L, and 12 (7.1%) had >800 U/L of LDH. Sixty-one percent of pregnant women (n=113) had CPI alterations. We found a correlation between LDH and CPI (p<0.001) and hypertension levels (p<0.05). Conclusions:Ourresults suggest a significant correlation between LDH and CPI in Peruvian pregnant women with preeclampsia allowing the diagnosis of >60% of cases. In addition, all corresponded to the third trimester of gestation, were ≤35 years-old and mostly multiparous.“